Interfacial mechanics : theories and methods for contact and lubrication - Wang, Qian, 1957-; Zhu, Dong (Mathematician) (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2020)
"This book discusses "tribological interface" that consists of two solid surfaces in contact with or without fluids in between. This specific type of interface is commonly seen in reality and extremely important in engineering applications. This book is written for engineering researchers and design engineers as well as graduate and senior undergraduate students. Mathematical treatments are tailored to a first degree in engineering often without rigorous descriptions and proofs. It focuses on the basic concepts, mathematic models, numerical solution procedures, major results and their physical meanings, as well as engineering applications"--
3.5.6.4 General Expressions3.6 Selected Basic Solutions; 3.6.1 Displacements Due to Concentrated Forces; 3.6.2 Surface Displacements Induced by Uniform Pressure; 3.6.2.1 2D Plane Strain Problem; 3.6.2.2 3 D Half-Space Problems; 3.6.3 Indentation by a Rigid Punch; 3.6.4 Frictionless Indentation by a Blunt Wedge or Cone; 3.6.5 A Sinusoidal Wavy Surface in Contact with a Flat; 3.6.5.1 2D Wavy Surface; 3.6.5.2 3D Wavy Surface; 3.7 Contact with Rough Surfaces; 3.7.1 A Stochastic Model for Rough Surface Contacts; 3.7.2 Empirical Formulae Based on Numerical Solutions for Rough Surface Contacts
OCLC-licensed vendor bibliographic record.
Keywords: Tribology -- Mathematics; Interfaces (Physical sciences) -- Mathematical models; Lubrication and lubricants; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Material Science